1996
DOI: 10.1046/j.1537-2995.1996.36596282589.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines in stored platelet concentrates

Abstract: Platelet factor 4, beta-thromboglobulin, and RANTES were released from platelets during storage and accumulated over time in the PCs. These chemokines might play a causative role in nonhemolytic transfusion reactions because of their inflammatory potential, but the clinical effects of the transfusion of PCs with high chemokine contents remain to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
3
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 23 publications
4
91
3
2
Order By: Relevance
“…Platelets release of chemokines may be one such role, i.e., RANTES is a major chemokine released from concentrated platelet preparation for transfusion and thus might be present in higher concentrations in the SPG-treated supernatant. 31) Furthermore, it is reported that IL-8 receptor exists on platelets. 32) Therefore SPG/SPG-OH-mediated IL-8 synthesis by leukocytes may be due to the synergistic action of the secreted products, RANTES, and membranous receptor, P-selectin, of platelets as well as released IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets release of chemokines may be one such role, i.e., RANTES is a major chemokine released from concentrated platelet preparation for transfusion and thus might be present in higher concentrations in the SPG-treated supernatant. 31) Furthermore, it is reported that IL-8 receptor exists on platelets. 32) Therefore SPG/SPG-OH-mediated IL-8 synthesis by leukocytes may be due to the synergistic action of the secreted products, RANTES, and membranous receptor, P-selectin, of platelets as well as released IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelets produce high quantities of chemokines, especially RANTES (45)(46)(47)(48)(49). Other studies performed by analyzing plasma͞serum levels of ␤-chemokines that did not show a positive effect of chemokines in HIV infection (50)(51)(52)(53)(54)(55)(56) probably were affected by this unspecific release.…”
Section: Discussionmentioning
confidence: 99%
“…To date, neither MIP-1a nor MIP-1b serum concentration has ever been correlated with HIV-1-related outcomes, 37 whereas circulating CCL5 (RANTES), especially as measured in plasma depleted of CCL5-rich platelets, 38,39 may be a useful biomarker in HIV-1 patients. 37,40,41 The elevated concentrations of serum CCL5 in our HIV-1-seropositive patients were quite consistent with all earlier observations.…”
Section: African Americans Othersmentioning
confidence: 99%